Numerical investigation of the effects of prosthetic aortic valve design on aortic hemodynamic characteristics - Zhu, Guang-Yu (2021)
The superior performance of single-point attached commissures (SPAC) molded valve design has been validated by several numerical, in vitro and in vivo animal studies. However, the impacts of the SPAC molded valve design on aortic hemodynamic environments are yet to be investigated. In this study, multiscale computational models were prepared by virtually implanting prosthetic aortic valves with SPAC tubular, SPAC molded and conventional designs into a patient-specific aorta, respectively. The impacts of the valve designs on efferent flow distribution, flow pattern and hemodynamic characteristics in the aorta were numerically investigated. The results showed that despite the overall flow phenomena being similar, the SPAC tubular valve exhibited a suboptimal performance in terms of higher spatially averaged wall shear stress (SAWSS) in ascending aorta (AAo), higher helix grade, stronger secondary flow mean secondary velocity in descending aorta, as well as more complex vortex distribution. The results from the current study extend the understanding of hemodynamic impacts of the valve designs, which would further benefit the optimization of the prosthetic aortic valve.